2015
DOI: 10.1089/jmf.2014.0060
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Hypolipidemic Effects of Peanut Skin Polyphenols

Abstract: Peanut skin is a rich source of polyphenols, such as proanthocyanidins. Peanut skin proanthocyanidins mainly consist of a subgroup called procyanidins. Peanut-based procyanidins contain oligomers of both type A and type B procyanidins. Recent studies have shown that peanut skin extracts exert protection against hepatic steatosis induced on rats fed with a high-fat diet. Studies have shown that proanthocyanidins protect against cardiovascular diseases (CVDs). The mechanism of CVD protection and hypolipidemic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Especially, compared to peanut seeds, germinated peanuts exhibit enhanced antioxidant activity [8]. These phenolic compounds have been associated with a wide range of health benefits such as the prevention of coronary heart diseases, different types of cancer, diabetes, and obesity [9]. Given the health benefits and commercial value, it is useful to comprehensively analyze the phenolic profiles and bioactivities of germinated peanuts.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, compared to peanut seeds, germinated peanuts exhibit enhanced antioxidant activity [8]. These phenolic compounds have been associated with a wide range of health benefits such as the prevention of coronary heart diseases, different types of cancer, diabetes, and obesity [9]. Given the health benefits and commercial value, it is useful to comprehensively analyze the phenolic profiles and bioactivities of germinated peanuts.…”
Section: Introductionmentioning
confidence: 99%
“…19 These health benefits are attributed to the trans-fatty acids, minerals, vitamins, fibers, and bioactive compounds present in the peanut. 20 The peanut skin, a byproduct of the peanut industry, contains high levels of polyphenols which exert potent antioxidant, 21 anti-inflammatory, 22 hypolipidemic, 23 and anti-bacterial, 24 effects. Despite these studies indicating that peanut skins are a potentially rich, safe, and inexpensive source of functional ingredients and could be helpful in combating microbial infections, their antiviral activity remains to be studied.…”
mentioning
confidence: 99%
“…Polyphenols can prevent reabsorption of bile acids in the small intestine by binding to them and triggering cholesterol destruction [25,26]. Bansode et al [27] concluded that low molecular weight polyphenols inhibited the intestinal transport of dietary cholesterol because of the decomposition of the bile acid-emulsified micellar structure in the intestines. In vitro bile acid binding activity is potentially related to the reduction in cholesterol content [18].…”
Section: In Vitro Hypocholesterolemic Effect Of Phenol Extracts Of DImentioning
confidence: 99%